2015
DOI: 10.1111/itor.12181
|View full text |Cite
|
Sign up to set email alerts
|

Workforce planning and financing on a production/capital discrete‐time model

Abstract: Traditionally, companies have considered production planning and financial commitments separately. Production planning involves planning when to produce how much of a product, while the financial commitment considers which loans to take and how to repay them. In the current difficult financial environment with new challenges and with different opportunities, such as short‐term flexible loans for paying salaries, these related problems must be considered together. In this paper, we model the two processes (prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Shortfalls in cash-balance are not permitted in all periods of the planning stream. Note that, as observed in [16], to concede shortfalls is the same as getting interest-free loans.…”
Section: Financial/workforce/production Planning Problemmentioning
confidence: 86%
See 3 more Smart Citations
“…Shortfalls in cash-balance are not permitted in all periods of the planning stream. Note that, as observed in [16], to concede shortfalls is the same as getting interest-free loans.…”
Section: Financial/workforce/production Planning Problemmentioning
confidence: 86%
“…The integration of cash-flows and workforce along the production process has also been discussed in [10,13,[15][16][17]. The formulation proposed in [13] includes financial aspects to support labor costs and production.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although some literature has shown that it is necessary to take financial factors into account when formulating production operation models, most researchers don't pay attentions to relative studies. Moreover, considering financial factors, existing papers mostly focus on traditional manufacturing systems and supply chain [32][33][34][35][36]. Few papers conduct the related research focusing on the closed-loop supply chain decisions and manufacturing/remanufacturing decisions.…”
Section: Literature Reviewmentioning
confidence: 99%